Exploring the lived experiences of maternal healthcare providers who contracted COVID-19: a descriptive phenomenological study - Victoria Bam; Abigail Kusi Amponsah; Joana Kyei-Dompim; Alberta Yemotsoo Lomotey; Rose Odotei Adjei; Dorothy Wilson (BMC Health Services Research)
Abstract Maternal healthcare providers are key stakeholders in safeguarding maternal and newborn health. This study employed a descriptive phenomenological design to explore the experiences of maternal healthcare providers who contracted the novel coronavirus disease, known as coronavirus disease 2019 (COVID-19), in Ghana. A purposive sample of seven maternal healthcare providers from a quasi-government hospital was engaged in face-to-face interviews. Interviews were audio-recorded, transcribed, and analysed using inductive thematic analysis. The results showed that participants experienced shock and grief related to the diagnosis of COVID-19; stigmatization and neglect by family members and colleagues; and psychological distress due to uncertainties about disease outcome, fear of dying, and infecting others. In addition, they experienced physical symptoms such as anosmia, chest pain, dyspnoea, and headache. Nevertheless, they shared positive experiences, including the opportunity to spend time with family, receiving support from family, colleagues, and superiors, and good treatment at isolation centres. Finally, the results highlighted how participants managed COVID-19 using both conventional drugs and traditional treatments; the preventive measures used; and recommendations for dealing with COVID-19. In conclusion, tailored and continuous psychosocial support for maternal healthcare providers is required to maintain their psychological well-being during future outbreaks. Based on the study findings, it is recommended that healthcare institutions prioritize the mental well-being of maternal healthcare providers during pandemics by providing accessible and culturally sensitive psychological support services. Furthermore, public health campaigns should focus on reducing the stigma associated with COVID-19 and promoting empathy and understanding towards healthcare workers.